A case of ampullary gangliocytic paraganglioma - Yang, Ju-Il (The Korean Association of Internal Medicine, 2014)
Gangliocytic paragangliomas (GPs) are rare tumors of the duodenum, presenting as single sessile or pedunculated polypoid masses. Clinical manifestations of duodenal GPs can vary from an incidental finding at endoscopy to frequent upper gastrointestinal bleeding caused by mucosal ulceration and abdominal pain. GPs are considered benign, but the disease can recur and spread to regional lymph nodes. A 41-year-old female presented with abdominal pain. Upper gastrointestinal endoscopy revealed a subepithelial tumor of the ampulla of Vater in the second portion of the duodenum. The tumor was resected using the endoscopic mucosal resection technique. The tumor was diagnosed as benign GP of the duodenum using histological and immunohistochemical staining procedures.